INNOVATIVE WAYS OF THE DEVELOPMENT OF THE SCIENTIFIC PERIODICAL EDITION OF THE ECONOMIC PROFILE - Ніколаєва, О. Г.; Тітомир, О. С. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The weak competitiveness of domestic science is one of the painful realities of the present. Experts in the field of science-research studies note the low publishing activity of Ukrainian scientists and the lack of knowledge of foreign colleagues in the results of domestic scientists. All this leads to insufficient integration of Ukrainian science into the world scientific community and complicates the cooperation of our scientists in the field of global scientific projects. One of the ways to intensify interaction with the international scientific community is to create competitive professional editions, with high-quality content, published in several languages and having analogies on the Internet. The article summarizes the experience of development of domestic scientific editions of the economic profile (EEP). The purpose of the publication of this work is to describe the internal and external environment of the innovative project of the site of the scientific national journal of the economic profile, namely the substantiation of the project of the electronic version of such edition (EVE). The influence of macroeconomic factors has been investigated. It has been shown that legal and technological factors affect the development of the publication and its electronic analogue positively, and the social, economic and political factors affect the project rather contradictory. The competitive advantages of a modern national economic journal are formulated, such as the availability of an electronic version of the magazine with support for multimedia, access to full-text archives, as well as a well-considered editorial policy and a stable reviewing system. The priority areas for the development of the EEP are the improvement of the quality of scientific publications and a registration of the journal in the science and technology databases of Web of Science and SCOPUS, which presupposes compliance with such requirements as, ISSN availability, periodicity of release, a stable review system, a well-considered editorial policy, a statement of compliance with publication ethics, wide enough geography of authors, presence of a site of a scientific journal (EVE), high quality of polygraphy.